SOCIO-POLITICAL INSTITUTIONAL DESIGN OF UKRAINIAN SOCIETY IN THE CONDITIONS OF CHANGES - Авксентьєва, Т.Г. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
A socio-political institutional design foresees certain configuration of parameters of society. It touches not only formal principles of organization but also character of relations between the basic subjects of political co-operation, rules of game and norms, valued orientations.Ukrainian political system and society as a whole need constructing of a new maintenance of parameters for acquisition of competitiveness. Among factors of steady development it is necessary to mark becoming of such indexes as responsibility of political power, its efficiency and definiteness of institutes of socio-political sphere.